Does acute aerobic exercise enhance selective attention, working memory, and problem-solving abilities in Alzheimer's patients? A sex-based comparative study - Ben Ayed, Ines; Ammar, Achraf; Aouichaoui, Chirine; Mezghani, Nourhen; Salem, Atef; Naija, Salma; Ben Amor, Sana; Trabelsi, Khaled; Jahrami, Haitham; Trabelsi, Yassine; El Massioui, Farid (Frontiers in Sports and Active Living, 2024)
The present study aimed to evaluate the effect of acute aerobic exercise on certain cognitive functions known to be affected by Alzheimer's disease (AD), with a particular emphasis on sex differences. A total of 53 patients, with a mean age of 70.54 ± 0.88 years and moderate AD, voluntarily participated in the study. Participants were randomly assigned to two groups: the experimental group (EG), which participated in a 20-minute moderate-intensity cycling session (60% of the individual maximum target heart rate recorded at the end of the 6-minute walk test); and the control group (CG), which participated in a 20-minute reading activity. Cognitive abilities were assessed before and after the physical exercise or reading session using the Stroop test for selective attention, the forward and backward digit span test for working memory, and the Tower of Hanoi task for problem-solving abilities. At baseline, both groups had comparable cognitive performance (p > 0.05 in all tests). Regardless of sex, aerobic acute exercise improved attention in the Stroop test (p < 0.001), enhanced memory performance in both forward (p < 0.001) and backward (p < 0.001) conditions, and reduced the time required to solve the problem in the Tower of Hanoi task (p < 0.001). No significant differences were observed in the number of movements. In contrast, the CG did not significantly improve after the reading session for any of the cognitive tasks (p > 0.05). Consequently, the EG recorded greater performance improvements than the CG in most cognitive tasks tested (p < 0.0001) after the intervention session. These findings demonstrate that, irrespective to sex, a single aerobic exercise session on an ergocycle can improve cognitive function in patients with moderate AD. The results suggest that acute aerobic exercise enhances cognitive function similarly in both female and male patients, indicating promising directions for inclusive therapeutic strategies.